Solar Panel Measurement System using Arduino with Bluetooth - Al Qindi M. Yusuf; Evanco Hollis N.P. Simangunsong; Indah Tria Wilyani; Iksan Bukhori (Journal of Electrical And Electronics Engineering, 2021)
This project aims to develop a measurement of solar energy using Arduino. In this research, two parameters that been measured are light intensity and the voltage. The light intensity was measured using light dependent resistor (LDR) sensor. The voltage was measured using the voltage divider because the voltage generated by the solar panel are large for the Arduino as receiver. These parameters as the input value for the Arduino and the output was display at the Arduino Bluetooth Controller. The Arduino Bluetooth controller display output of the light intensity and the voltage value. The purpose of using Arduino is to convert the analog input of parameter to the digital output and display via Bluetooth .